The Fake News Sharing in Social Media During Covid-19 from Users and Gratification 2.0 Theory Perspective: Malaysian Users as example - Dan , He; Sannusi, Shahrul Nazmi; Rizal, Ammar Redza Bin Ahmad (Journal of Ecohumanism, 2024)
Amidst the COVID-19 pandemic, the proliferation of fake news has raised significant concerns globally. This research aims to examine the influence of disseminating false news on social media channels throughout the pandemic period in Malaysia, utilising the perspective of the uses and gratification 2.0 theory. Employing a close-ended survey questionnaire for data collection and employing statistical methods, 308 respondents from Malaysia were included in the study. The findings indicated that interactivity and modality significantly influenced fake news sharing among the respondents, whereas social media usage negatively moderated the association between navigation and fake news sharing. The findings indicate that interactivity and modality increased sharing, but social media usage negatively moderates the link between navigation and sharing. The study acknowledges limitations such as the small sample size of 308 respondents from Malaysia due to time constraints, and its focus on the Uses and Gratification 2.0 theory. Nevertheless, these results highlight the significance of comprehending the mechanisms involved in the spread of fake news on social media platforms during pandemic events.